Copper-catalysed Csp3–Csp cross-couplings between cyclobutanone oxime esters and terminal alkynes induced by visible light. Issue 34 (25th March 2020) - Zhao, Binlin; Wu, Yixiao; Yuan, Yu; Shi, Zhuangzhi
Abstract : A novel transformation for the construction of Csp 3 –Csp bonds was achieved via a photo-induced copper-catalysed C–C bond cleavage. Abstract : A novel transformation for the construction of Csp 3 –Csp bonds was achieved via a photo-induced copper-catalysed C–C bond cleavage. This approach was applied to prepare a series of highly functionalized alkynyl nitriles using readily available cyclobutanones and terminal alkynes. Mechanistic exploration showed that the in situ generated copper acetylide complex is an effective photosensitive catalyst to promote the C–C bond cleavage of cycloketoxime esters through a radical process.